Cornerstones of a renewable energy law for emerging markets in South America - Kissel, J.; Hanitsch, Rolf; Krauter, Stefan (Energy Policy)

Yield prediction and comparison of a-Si modules - Preiss, A.; Krauter, Stefan (Proceedings of the 24th European Photovoltaic Solar Energy Conference and Exhibition, Hamburg (Deutschland), 21.–25. September 2009, S. 2846–2849)

From Design Models to Test Models by Means of Test Ideas - Mlynarski, Michael; Güldali, Baris; Späth, Melanie; Engels, Gregor (MoDeVVa '09: Proceedings of the 6th International Workshop on Model-Driven Engineering, Verification and Validation)

Automatic Generation of Behavioral Code - too ambitious or even unwanted? - Engels, Gregor (First European Workshop on Behaviour Modelling in Model Driven Architecture (BM-MDA))

Inspection Effectiveness for Different Quality Attributes of Software Requirement Specifications - An Industrial Case Study - Salger, Frank; Engels, Gregor; Hofmann, Alexander (Proceedings of the ICSE Workshop on Software Quality (WoSQ 2009))

An Integrated Quality Assurance Framework for Specifying Business Information Systems - Salger, Frank; Sauer, Stefan; Engels, Gregor (Proceedings of the Forum at the CAiSE 2009 Conference, Amsterdam (The Netherlands))
The software specification acts as a bridge between customers, architects, software developers and testers. If information gets lost or distorted when building this bridge, the wrong system will be built or the system will not be built in time and budget–or both! Standards and recommendations give advice on how to structure specifications or check software-engineering artefacts with reviews or inspections. But these constructive and analytical approaches are not well integrated with each other. Moreover, they are often too generic to efficiently support the specification of particular system types. In this paper, we present the integrated “specification framework” of Capgemini sd&m. It consists of our specification method for business information systems (BIS) and its concerted analytical counterpart, the “specification quality gate”. Since this framework is tailored to the specification of large BIS, it allows a quick ramp-up phase for software engineering projects without the need for extensive tailoring or extension.

Towards Generalizing Visual Process Pattern - Soltenborn, Christian; Engels, Gregor (Proceedings of the 1st International Workshop on Visual Formalisms for Patterns (VFfP 2009), Corvallis, OR (USA))
Visual Process Pattern (VPP) is a visual language to describe constraints on the behavior of UML Activities. They have been developed for the sake of formulating and verifying requirements on business process models (with Activities being one possible description language). In the VPP approach, a visual pattern is translated into an LTL formula, which can then be verified against a transition system describing the behavior of the Activity under consideration. In this paper, we aim at generalizing VPP. We show how to formulate patterns more generally, using either concrete or abstract syntax of the behavioral model under consideration. Additionally, we describe how these more general patterns can be verified against a model’s behavior.

Lösungsorientierte Software Produktlinienentwicklung in heterogenen Systemlandschaften - von der Maßen, Thomas; Wübbeke, Andreas (Proceedings of Produktlinien im Kontext (PIK09))

Inversion-asymmetry-induced spin splitting observed in the quantum oscillatory magnetization of a two-dimensional electron system - Wilde, M. A.; Reuter, Dirk; Heyn, Ch.; Wieck, A. D.; Grundler, D. (Physical Review B)

Nonlocal Aharonov–Bohm conductance oscillations in an asymmetric quantum ring - Buchholz, S. S.; Fischer, S. F.; Kunze, U.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Ellipsoidal InAs quantum dots observed by cross-sectional scanning tunneling microscopy - Blokland, J. H.; Bozkurt, M.; Ulloa, J. M.; Reuter, Dirk; Wieck, A. D.; Koenraad, P. M.; Christianen, P. C. M.; Maan, J. C. (Applied Physics Letters)

Collective single-mode precession of electron spins in an ensemble of singly charged (In,Ga)As/GaAs quantum dots - Greilich, A.; Spatzek, S.; Yugova, I. A.; Akimov, I. A.; Yakovlev, D. R.; Efros, Al. L.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Ultrafast optical rotations of electron spins in quantum dots - Greilich, A.; Economou, Sophia E.; Spatzek, S.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Reinecke, T. L.; Bayer, M. (Nature Physics)

Long-Term Hole Spin Memory in the Resonantly Amplified Spin Coherence ofInGaAs/GaAsQuantum Well Electrons - Yugova, I. A.; Sokolova, A. A.; Yakovlev, D. R.; Greilich, A.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review Letters)

Inversion-asymmetry-induced spin splitting observed in the quantum oscillatory magnetization of a two-dimensional electron system - Wilde, M. A.; Reuter, Dirk; Heyn, Ch.; Wieck, A. D.; Grundler, D. (Physical Review B)

Using a two-dimensional electron gas to study nonequilibrium tunneling dynamics and charge storage in self-assembled quantum dots - Marquardt, B.; Geller, M.; Lorke, A.; Reuter, Dirk; Wieck, A. D. (Applied Physics Letters)

Conversion of bound excitons to free excitons by surface acoustic waves - Völk, S.; Wixforth, A.; Reuter, Dirk; Wieck, A. D.; Ebbecke, J. (Physical Review B)

Measurement of the Knight field and local nuclear dipole-dipole field in an InGaAs/GaAs quantum dot ensemble - Auer, T.; Oulton, R.; Bauschulte, A.; Yakovlev, D. R.; Bayer, M.; Verbin, S. Yu.; Cherbunin, R. V.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Lateral electron tunnelling spectroscopy in etched GaAs/AlGaAs-based nanostructures - Fischer, S F; Deborde, J L; Kunze, U; Reuter, Dirk; Wieck, A D (Journal of Physics: Conference Series)

Lateral electron tunnelling spectroscopy in etched GaAs/AlGaAs-based nanostructures - Fischer, S F; Deborde, J L; Kunze, U; Reuter, Dirk; Wieck, A D (Journal of Physics: Conference Series)

Magnetic barrier in a two-dimensional hole gas - Cerchez, M.; Heinzel, T.; Reuter, Dirk; Wieck, A.D. (Superlattices and Microstructures)

Carrier relaxation dynamics in self-assembled semiconductor quantum dots - Kurtze, H.; Seebeck, J.; Gartner, P.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M.; Jahnke, F. (Physical Review B)

Verlässlichkeit selbstoptimierender Systeme -- Potenziale nutzen und Risiken vermeiden - Dell'Aere, Alessandro; Hirsch, Martin; Klöpper, Benjamin; Koester, Markus; Krup, Alexander; Krüger, Martin; Müller, Thomas; Oberthür, Simon; Pook, Sebastian; Priesterjahn, Claudia; Romaus, Christoph; Schmidt, Alexander; et al.
Gegenstand des Sonderforschungsbereichs 614 "Selbstoptimierende Systeme des Maschinenbaus" sind maschinenbauliche Systeme von morgen. Diese werden aus Konfigurationen von Systemelementen mit einer inhärenten Teilintelligenz bestehen. Das Verhalten des Gesamtsystems wird durch die Kommunikation und Kooperation der intelligenten Systemelemente geprägt sein. Selbstoptimierung ermöglicht handlungsfähige Systeme mit inhärenter "Intelligenz", die in der Lage sind, selbständig und flexibel auf veränderte Betriebsbedingungen zu reagieren. Die Vision des SFB 614 ist eine neue Schule des Entwurfs von intelligenten mechatronischen Systemen. Diese neue Schule beruht auf einem Instrumentarium bestehend aus Vorgehensmodellen, Entwurfsmethoden und -werkzeugen und Praktiken. Das Instrumentarium entsteht im Wechselspiel mit der Entwicklung von anspruchsvollen Demonstratoren, die als repräsentativ für künftige Erzeugnisse des Maschinenbaus und verwandter Branchen wie der Automobilindustrie und der Medizintechnik gelten können. Vor diesem Hintergrund zeichnet sich die Herausforderung ab, derartige Systeme zuverlässig zu gestalten. Wir haben statt Zuverlässigkeit den Begriff Verlässlichkeit gewählt, weil er die Aspekte Verfügbarkeit, Zuverlässigkeit, Sicherheit und Vertraulichkeit umfasst und somit unser Anliegen auf den Weg zu den Erzeugnissen von morgen treffend zum Ausdruck bringt. Das vorliegende Buch ist das Ergebnis der projektübergreifenden interdisziplinären Zusammenarbeit in dem Arbeitskreis "Sicherheit und Stabilität" des SFB 614. Es gibt eine gut aufbereitete Einführung in den umfassenden Themenkomplex Verlässlichkeit und zeigt anhand von anspruchsvollen Beispielen der fortgeschrittenen Mechatronik, wie komplexe, stark durch Informations- und Kommunikationstechnik geprägte technische Systeme verlässlich gestaltet werden können. Dabei wird deutlich, dass das Wirkparadigma der Selbstoptimierung nicht nur größere Anstrengungen erfordert, um Verlässlichkeit zu erreichen, sondern auch neue Möglichkeiten für mehr Verlässlichkeit eröffnet.

Reinforcement Learning for Blackjack - Kakvi, Saqib (Lecture Notes in Computer Science)

Assmann, A.: Einführung in die Kulturwissenschaft - Tönnies, Merle (Anglistik. International Journal of English Studies)

Lionel Johnson - Flotmann, Christina (Kindlers Literaturlexikon)

Modellbasierte Entwicklung piezoelektrischer Trägheitsmotoren - Hunstig, Matthias; Hemsel, Tobias (6. Paderborner Workshop Entwurf mechatronischer Systeme)
Die Entwicklung piezoelektrischer Trägheitsmotoren basiert derzeit auf Erfahrungswissen und Prototypenbau. Es existiert kein allgemeines Modell und keine Methodik für die systematische Entwicklung dieser Motoren. In diesem Beitrag stellen wir einen Ansatz zur Entwicklung einer solchen Methodik und den von uns aufgebauten Versuchsmotor vor. Der Motor ist modular aufgebaut; er besteht im Wesentlichen aus einer piezoelektrischen Antriebseinheit, einem Antriebsstab und dem zu bewegenden Schlitten. Eine wesentliche Aufgabe bei der modellbasierten Entwicklung von Trägheitsmotoren ist die hinreichende Beschreibung des dynamischen Verhaltens der Antriebseinheit. Um ein geeignetes Modell zu finden, bzw. um nachzuweisen, dass einfache parametrische Modelle genügen, wird die Antriebseinheit des Motors detailliert untersucht. Es zeigt sich, dass der derzeitige Aufbau eine Reihe von Nachteilen aufweist, die durch eine teilweise Neukonstruktion der Antriebseinheit beseitigt oder zumindest entschärft werden können.
Keywords: Piezoelektrischer Tr{\

Probabilistic planning integrated in a multi-level dependability concept for mechatronic systems - Klöpper, Benjamin; Sondermann-Wölke, Christoph; Romaus, Christoph; Vöcking, Henner (Computational Intelligence in Control and Automation, 2009. CICA 2009. IEEE Symposium on)
Self-optimizing mechatronic systems are a new class of technical systems. On the one hand, new challenges regarding dependability arise from their additional complexity and adaptivity. On the other hand, their abilities enable new concepts and methods to improve the dependability of mechatronic systems. This paper introduces a multi-level dependability concept for self-optimizing mechatronic systems and shows how planning can be used to improve the availability and reliability of systems in the operating stages.
Keywords: multilevel dependability concept; probabilistic planning; self-optimizing mechatronic systems; systems reliability; mechatronics; planning (artificial intelligence); self-adjusting systems

Potenzialfeldmethoden zur Fahrzeugführung für Fahrerassistenzsysteme zum automatisierten Fahren - Sattel, Thomas; Hesse, Tobias; Sondermann-Wölke, Christoph; Hüfner, Thorsten (memo - mechatronik mobil)

Verlässlichkeit im aktiven selbstoptimierenden Spurführungsmodul eines schienengebundenen Fahrzeugs - Sondermann-Wölke, Christoph; Geisler, Jens; Hirsch, Martin; Hemsel, Tobias (Entwurf mechatronischer Systeme)
Die Integration von Selbstoptimierung in mechatronische Systeme beinhaltet sowohl Risiken als auch Potenziale für die Verlässlichkeit. Die Risiken entstehen durch die Selbstoptimierung in den komplexen Systemen, da das Systemverhalten nur begrenzt im Voraus vorhersehbar ist. Daher wurde innerhalb des Sonderforschungsbereichs 614 ''Selbstoptimierende Systeme des Maschinenbaus" ein mehrstufiges Verlässlichkeitskonzept entworfen, welches das Ziel Verlässlichkeit stärker im Zielsystem verankert. In diesem Beitrag wird zum einen das erarbeitete Verlässlichkeitskonzept und zum anderen die Anwendung dieses Konzepts innerhalb des aktiven Spurführungsmoduls eines schienengebundenen Fahrzeugs vorgestellt. Um Programmierfehler auszuschließen wurde das Verlässlichkeitskonzept modelliert und über Model Checking verifiziert. Anhand von Simulationsergebnissen wird gezeigt, wie durch das mehrstufige Verlässlichkeitskonzept auf einen Ausfall eines Wirbelstromsensors des aktiven Spurführungsmoduls reagiert werden kann.
Keywords: Verlässigkeit

Menschliche Unzuverlässigkeit als Grundlage für den Entwurf von Kollisionsvermeidungssystemen. - Sondermann-Wölke, Christoph; Hesse, Tobias; Sattel, Thomas; Hemsel, Tobias (24. Tagung Technische Zuverlässigkeit (TTZ 2009) - Entwicklung und Betrieb zuverlässiger Produkte, Leonberg)

Towards the Integration of Condition Monitoring in Self-Optimizing Function Modules - Sondermann-Wölke, Christoph; Sextro, Walter (Future Computing, Service Computation, Cognitive, Adaptive, Content, Patterns, 2009. COMPUTATIONWORLD '09. Computation World:)
New mechatronic systems, called self-optimizing systems, are able to adapt their behavior according to environmental, user and system specific influences. Self-optimizing systems are complex and due to their non-deterministic behavior comprise hidden risks, which cannot be foreseen in the design phase of the system. Therefore, this paper presents modifications of the current condition monitoring policy, to be able to cope with this new kind of systems. Beside avoiding critical situations evoked by self-optimization, the proposed concept uses self-optimization to increase the dependability of the system. In this case, the concept is applied to the active guidance module of an innovative rail-bound vehicle.
Keywords: condition monitoring; mechatronic systems; rail bound vehicle; rail guidance module; self-optimization; self-optimizing function modules; condition monitoring; mechatronics; railway rolling stock; self-adjusting systems

Nanoscale Surface Patterning of Silicon Using Local Swelling Induced by He Implantation through NSL-Masks - Fischer, Frederic J.C.; Weinl, Michael; Lindner, Jörg; Stritzker, Bernd (MRS Proceedings)
A novel technique to form periodically nanostructured Si surface morphologies based on nanosphere lithography (NSL) and He ion implantation induced swelling is studied in detail. It is shown that by implantation of keV He ions through the nanometric openings of NSL masks regular arrays of hillocks and rings can be created on silicon surfaces. The shape and size of these surface features can be easily controlled by adjusting the ion dose and energy as well as the mask size. Feature heights of more than 100 nm can be obtained, while feature distances are typically 1.15 or 2 (hillock or ring) nanosphere radii, which are chosen to be between 100 and 500 nm in this study. Atomic force and scanning electron microscopy measurements of the surface morphology are supplemented by cross-sectional transmission electron microscopy, revealing the inner structure of hillocks to consist of a central cavity surrounded by a hierarchical arrangement of smaller voids. The surface morphologies developed here have the potential to be useful for fixing and separating nano-objects on a silicon surface.

Indirect Dephasing Channel for Optically Controlled Spin in a Single Quantum Dot - Grodecka, Anna; Machnikowski, Pawel; Förstner, Jens (Advances in Optical Sciences Congress)
We show that an optically driven carrier spin undergoes indirect dephasing even in the absence of spin-reservoir coupling and illustrate it for phonon-induced decoherence during optical spin rotation in a single quantum dot.
Keywords: tet_topic_qd

Indirect spin dephasing via charge-state decoherence in optical control schemes in quantum dots - Grodecka, A.; Machnikowski, P.; Förstner, Jens (Physical Review A)
We demonstrate that an optically driven spin of a carrier in a quantum dot undergoes indirect dephasing via conditional optically induced charge evolution even in the absence of any direct interaction between the spin and its environment. A generic model for the indirect dephasing with a three-component system with spin, charge, and reservoir is proposed. This indirect decoherence channel is studied for the optical spin manipulation in a quantum dot with a microscopic description of the charge-phonon interaction taking into account its non-Markovian nature.
Keywords: tet_topic_qd

Structural characterization of cubic and hexagonal GaN thin films grown by IBA–MBE on SiC/Si - Häberlen, M.; Gerlach, J.W.; Murphy, B.; Lindner, Jörg; Stritzker, B. (Journal of Crystal Growth)
Buried ion beam synthesized 3C-SiC layers were revealed to the surface of silicon wafers to provide lattice matched substrates for GaN thin film epitaxy. Both epitaxial SiC/Si(1 1 1) and SiC/Si(0 0 1) growth surfaces with either six- or four-fold crystal symmetry, respectively, were formed. GaN thin film growth was achieved by ion beam assisted molecular beam epitaxy (IBA–MBE) which – owing to the energy and momentum transfer of the ions – allows to deposit epitaxial thin films at particularly low growth temperatures where both the stable hexagonal and the metastable cubic polytype of GaN can be formed. It is shown by X-ray diffraction (XRD) and cross-sectional transmission electron microscopy (XTEM) that using appropriate fluxes of Ga atoms both purely hexagonal and purely cubic GaN films can be grown epitaxially on SiC/Si(1 1 1) and SiC/Si(0 0 1), respectively. Thereby Ga rich growth conditions seem to stabilize the formation of the cubic polytype. It is obvious from XTEM studies that the high density of crystal defects in the SiC layer is not transferred onto the growing GaN films and that the crystalline quality of GaN films improves with increasing film thickness. The influence of surface roughness and wettability, interfacial cavities and the nucleation of twin-type defects at the GaN/SiC interface on the crystalline quality of the GaN thin films is discussed.

Non-polar cubic AlGaN/GaN HFETs grown by MBE on Ar+implanted 3C-SiC (001) - Tschumak, Elena; Lindner, Jörg; Bürger, M.; Lischka, K.; Nagasawa, H.; Abe, M.; As, Donald (physica status solidi (c))
The growth of cubic group III-nitrides is a direct way to eliminate polarization effects, which inherently limit the fabrication of normally-off heterojunction field-effect transistors (HFETs) in GaN technology. HFET structures were fabricated of non-polar cubic AlGaN/GaN hetero layers grown by plasma assisted molecular beam epitaxy (MBE) on free standing 3C-SiC (001). The electrical insulation of 3C-SiC was realised by Ar+ implantation before c-AlGaN/GaN MBE. The structural properties of the epilayers were studied by highresolution x-ray diffraction (HRXRD). HFETs with normally off and normally-on characteristics were fabricated of cubic AlGaN/GaN. Capacitance-voltage (CV) characteristics of thegate contact were performed to detect the electron channel at the c-AlGaN/GaN hetero interface.

Direction-selective optical transmission of 3D fcc photonic crystals in the microwave regime - Üpping, J.; Miclea, P.T.; Wehrspohn, R.B.; Baumgarten, T.; Greulich-Weber, Siegmund (Photonics and Nanostructures - Fundamentals and Applications)
Three-dimensional (3D) photonic crystal exhibit direction-selective transmission with respect to the center frequency of the stop gap. As a model system, the stop gap of a 3D fcc inverted-opal photonic crystal is studied in the microwave regime in detail using 3D polyamide models. The difference in the direction-selective transmittance between crystals grown in two different high symmetry directions is experimentally shown and compared to numerical simulations.

Textile Solar Cells Based on SiC Microwires - Greulich-Weber, Siegmund; Zöller, M.; Friedel, B. (Materials Science Forum)
The solar cell concept presented here is based on 3C-SiC nano- or microwires and conju¬gated polymers. Therefore the silicon carbide wires are fabricated by a sol-gel route including a car-bothermal reduction step, allowing growth with predetermined uniform diameters between 0.1 and 2μm and lengths up to several centimetres. The design of our photovoltaic device is therein based on a p-i-n structure, well known e.g. from silicon photovoltaics, involving an intrinsic semiconduc¬tor as the central photoactive layer, sandwiched between two complementary doped wide-bandgap semiconductors giving the driving force for charge separation. In our case the 3C-SiC microwires act as the electron acceptor and simultaneously as carrier material for all involved components of the photovoltaic element.

Bottom-Up Routes to Porous Silicon Carbide - Greulich-Weber, Siegmund; Friedel, B. (Materials Science Forum)
We report on constructive methods providing a large range of high purity porous SiC products. All methods are based on modified sol-gel processes combined with carbothermal re¬duction. We obtain monodisperse regular pores of well defined diameters by using carbon sphere templates which are removed after SiC infiltration. A different way is a sol-gel based conversion of graphite bodies into SiC, which transfers the porosity from the graphite matrix into the final SiC product. Thus a large variety of porosity features are available, originating either from natural poro¬sity of graphite or from priorly created nano-/ microstructures in the carbonaceous base material. Whereas all our pristine porous sol-gel derived silicon carbide products are semi-insulating, doping is possible, during the growth to modifiy the electrical and optical properties.

Regular surface patterns by local swelling induced by He implantation into silicon through nanosphere lithography masks - Lindner, Jörg; Seider, C.; Fischer, F.; Weinl, M.; Stritzker, B. (Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms)
Nanopatterning of silicon surfaces by means of He+ ion implantation through self-organized colloidal masks is reported for the first time. Nanosphere lithography (NSL) masks with mask openings of 46– 230 nm width were deposited on Si(100) wafers. He+ ions were implanted through these masks in order to induce a local cavity formation and Si surface swelling. The surface morphology and the subsurface structure were studied using atomic force microscopy (AFM) and cross-sectional transmission electron microscopy (XTEM), respectively, as a function of mask and implantation parameters. It is demonstrated that regular arrays of both individual hillocks and trough-like circular rings can be generated.

Radiation suppressed oxide growth in the system Ni–Ti–O - Lutz, J.; Gerlach, J.W.; Lindner, Jörg; Assmann, W.; Mändl, S. (Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms)
The formation of a thick protective oxide layer on NiTi by plasma immersion ion implantation (PIII) for medical devices is an established technology on the laboratory scale. It is shown here that by pre-implantation with either 180 keV Ni or low fluence of 190 MeV Au ions, a radiation suppressed growth of the oxide layer of up to 40% is observed. At higher Au fluence and higher PIII temperatures, this changes into an enhancement of 25–40%. Different amorphisation mechanisms or disorder formation is proposed as the underlying effect.

Spin-Coupling in Heavily Nitrogen-Doped 4H-SiC - Savchenko, D.V.; Pöppl, Andreas; Kalabukhova, Ekaterina N.; Greulich-Weber, Siegmund; Rauls, Eva; Schmidt, Wolf Gero; Gerstmann, Uwe (Materials Science Forum)
EPR and ESE in nitrogen doped 4H- and 6H-SiC show besides the well known triplet lines of 14N on quasi-cubic (Nc,k) and hexagonal (Nc,h) sites additional lines (Nx) of comparatively low intensity providing half the hf splitting of Nc,k. Frequently re-interpreted as spin-forbidden lines, arising from Nc,k pairs and triads or resulting from hopping conductivity, only recently the theoretical calculation of the corresponding g-tensors lead to a tentative model of distant NC donor pairs on inequivalent lattice sites which are coupled to S = 1 assuming a fine-structure splitting too small to be observed in the EPR and ESE experiments. In this work, we present ESE nutation measurements confirming S = 1 for the Nx center. Analysing the nutation frequencies in comparison with that of the Nc,k (S = 1/2) spectrum as well as the line width of ESE and EPR spectra we obtain a rough estimate between 5×104 cm-1 and 50×104 cm-1 for the fine-structure splitting demonstrating efficient spin-coupling between nitrogen donors in 4H-SiC.

Vacancy clusters created via room temperature irradiation in 6H-SiC - Scholle, A.; Greulich-Weber, S.; Rauls, E.; Schmidt, W.G.; Gerstmann, U. (Physica B: Condensed Matter)
In non-annealed 6H-SiC samples that were electron irradiated at low temperature, a new EPR signal due to a S =1 defect center with exceptionally large zero-field splitting (D= +652104cm1,E=8104cm1) has been observed under illumination. A positive sign of D demonstrates that the spin–orbit contribution to the zero-field splitting exceeds by far that of the spin–spin interaction. A principal axis of the fine-structure tilted by 59 1 against the crystal c -axis as well as the exceptionally high zero-field splitting D can be qualitatively understood by the occurrence of additional close-lying defect levels in defect clusters resulting in comparatively large second-order spin–orbit coupling. A tentative assignment to vacancy clusters is supported by the observed annealing behavior.

GaN-based LEDs grown on 6-inch diameter Si (111) substrates by MOVPE - Zhu, D.; McAleese, C.; McLaughlin, K. K.; Häberlen, M.; Salcianu, C. O.; Thrush, E. J.; Kappers, M. J.; Phillips, W. A.; Lane, P.; Wallis, D. J.; Martin, T.; Astles, M.; et al. (Light-Emitting Diodes: Materials, Devices, and Applications for Solid State Lighting XIII)
The issues and challenges of growing GaN-based structures on large area Si substrates have been studied. These include Si slip resulting from large temperature non-uniformities and cracking due to differential thermal expansion. Using an AlN nucleation layer in conjunction with an AlGaN buffer layer for stress management, and together with the interactive use of real time in-situ optical monitoring it was possible to realise flat, crack-free and uniform GaN and LED structures on 6-inch Si (111) substrates. The EL performance of processed LED devices was also studied on-wafer, giving good EL characteristics including a forward bias voltage of ~3.5 V at 20 mA from a 500 μm x 500 μm device.

Characterisation of nanostructured materials for electronic and photonic information processing - Lindner, Jörg

Ion Implantation: Fundamental Aspects and Recent Applications - Lindner, Jörg

Ionenstrahlmodifikation kleiner Oberflächenbereiche mittels selbstorganisierter Nanomasken - Lindner, Jörg

Synthesis of 2D-Nanostructured ZnO Thin Films using Nanosphere Lithography and Sputter Deposition - Reichardt, F.; Weinl, M.; Gogel, D.; Wätje, K.; Wixforth, A.; Stritzker, B.; Lindner, Jörg

PAS 1094: Hybride Wertschöpfung --- Integration von Produktion und Dienstleistung. - Institut für Normung e.V., Deutsches

Determinanten früher Internationalisierung: eine Meta-Analyse. - Schwens, C; Kabst, Rüdiger (Zeitschrift für Betriebswirtschaft (ZfB).)

Early Internationalization: A Transaction Cost Economics and Structural Embeddedness Perspective. - Schwens, C; Kabst, Rüdiger (Journal of International Entrepreneurship (JIE).)

How Early Opposed to Late Internationalizers Learn: Experience of Others and Paradigms of Interpretation. - Schwens, C; Kabst, Rüdiger (International Business Review (IBR))

Internationalisierung junger Technologieunternehmen: Der moderierende Einfluss der „Liabilities of Foreignness.“ - Baum, M; Schwens, C; Kabst, Rüdiger (Zeitschrift für Betriebswirtschaft (ZfB).)

Organisational adoption of e-HRM in Europe: An empirical exploration of major adoption factors. - Strohmeier, S; Kabst, Rüdiger (Journal of Managerial Psychology.)

Organizational Commitment und Job Involvement in Deutschland und Südkorea: Eine bedürfnisorientierte empirische Analyse. - Park, Y K; Kabst, Rüdiger; Steinmetz, Holger; Turner, M (Managementforschung.)

Testing Measurement Invariance Using Multigroup CFA: Differences between Educational Groups in Human Values Measurement. - Steinmetz, H; Schmidt, P; Tina-Booh, A; Schwartz, S H; Wieczorek, S (Quality and Quantity.)

The Cultural Dependence of Vocational Training. - Beck, N; Kabst, Rüdiger; Walgenbach, P (Journal of International Business Studies (JIBS).)

Elektronische Wahlen: Verifizierung vs. Zertifizierung - Volkamer, Melanie; Schryen, Guido; Langer, Lucie; Schmidt, Axel; Buchmann, Johannes (Workshop Elektronische Wahlen, elektronische Teilhabe, Societyware, 39th GI-Jahrestagung)
Der Beitrag diskutiert die kontroversen Ansätze ? Verifizierung versus Evaluation/Zertifizierung ? zur Sicherung elektronischer Wahlen mit Wahlgeräten. Dabei spielt das Urteils des Bundesverfassungsgerichts [BVG099] eine zentrale Rolle. Hierin wird entschieden, dass die Zertifizierung des Wahlgerätes nicht ausreicht und es werden Verifizierungsfunktionen gefordert, die den Wählern die Möglichkeit geben sich von der Integrität des Wahlergebnisses zu überzeugen. Der Beitrag zeigt auf, dass auch mit der Implementierung entsprechender Verifizierungsfunktionen nicht auf Zertifizierung verzichtet werden kann, da an ein Wahlgerät auch andere Anforderungen wie etwa hinsichtlich des Wahlgeheimnisses gestellt werden. Es wird außerdem die Frage diskutiert, warum der Zertifizierung hinsichtlich dieser zusätzlichen Anforderungen vertraut werden kann, während dies nicht der Fall bei der Integritätsanforderung ist.

Security in Large-Scale Internet Elections: A Retrospective Analysis of Elections in Estonia, The Netherlands, and Switzerland - Schryen, Guido; Rich, Eliot (IEEE Transactions on Information Forensics & Security)
Remote voting through the Internet provides convenience and access to the electorate. At the same time, the security concerns facing any distributed application are magnified when the task is so crucial to democratic society. In addition, some of the electoral process loses transparency when it is encapsulated in information technology. In this paper, we examine the public record of three recent elections that used Internet voting. Our specific goal is to identify any potential flaws that security experts would recognize, but may have not been identified in the rush to implement technology. To do this, we present a multiple exploratory case study, looking at elections conducted between 2006 and 2007 in Estonia, Netherlands, and Switzerland. These elections were selected as particularly interesting and accessible, and each presents its own technical and security challenges. The electoral environment, technical design and process for each election are described, including reconstruction of details which are implied but not specified within the source material. We found that all three elections warrant significant concern about voter security, verifiability, and transparency. Usability, our fourth area of focus, seems to have been well-addressed in these elections. While our analysis is based on public documents and previously published reports, and therefore lacking access to any confidential materials held by electoral officials, this comparative analysis provides interesting insight and consistent questions across all these cases. Effective review of Internet voting requires an aggressive stance towards identifying potential security and operational flaws, and we encourage the use of third party reviews with critical technology skills during design, programming, and voting to reduce the changes of failure or fraud that would undermine public confidence.
Keywords: e-voting; Internet voting; Internet election; security; verifiability; RIES; Estonia; Neuchâtel

Open Source vs. Closed Source Software: Towards Measuring Security - Schryen, Guido; Kadura, Rouven (24th Annual ACM Symposium on Applied Computing)
The increasing availability and deployment of open source software in personal and commercial environments makes open source software highly appealing for hackers, and others who are interested in exploiting software vulnerabilities. This deployment has resulted in a debate ?full of religion? on the security of open source software compared to that of closed source software. However, beyond such arguments, only little quantitative analysis on this research issue has taken place. We discuss the state-of-the-art of the security debate and identify shortcomings. Based on these, we propose new metrics, which allows to answer the question to what extent the review process of open source and closed source development has helped to fix vulnerabilities. We illustrate the application of some of these metrics in a case study on OpenOffice (open source software) vs. Microsoft Office (closed source software).
Keywords: Open source software; Closed source software; Security; Metrics

A comprehensive and comparative analysis of the patching behavior of open source and closed source software vendors - Schryen, Guido (5th International Conference on IT Security Incident Management & IT Forensics)
While many theoretical arguments against or in favor of open source and closed source software development have been presented, the empirical basis for the assessment of arguments is still weak. Addressing this research gap, this paper presents a comprehensive empirical investigation of the patching behavior of software vendors/communities of widely deployed open source and closed source software packages, including operating systems, database systems, web browsers, email clients, and office systems. As the value of any empirical study relies on the quality of data available, this paper also discusses in detail data issues, explains to what extent the empirical analysis can be based on vulnerability data contained in the NIST National Vulnerability Database, and shows how data on vulnerability patches was collected by the author to support this study. The results of the analysis suggest that it is not the particular software development style that determines patching behavior, but rather the policy of the particular software vendor.

Security of open source and closed source software: An empirical comparison of published vulnerabilities - Schryen, Guido (15th Americas Conference on Information Systems)
Reviewing literature on open source and closed source security reveals that the discussion is often determined by biased attitudes toward one of these development styles. The discussion specifically lacks appropriate metrics, methodology and hard data. This paper contributes to solving this problem by analyzing and comparing published vulnerabilities of eight open source software and nine closed source software packages, all of which are widely deployed. Thereby, it provides an extensive empirical analysis of vulnerabilities in terms of mean time between vulnerability disclosures, the development of disclosure over time, and the severity of vulnerabilities, and allows for validating models provided in the literature. The investigation reveals that (a) the mean time between vulnerability disclosures was lower for open source software in half of the cases, while the other cases show no differences, (b) in contrast to literature assumption, 14 out of 17 software packages showed a significant linear or piecewise linear correlation between time and the number of published vulnerabilities, and (c) regarding the severity of vulnerabilities, no significant differences were found between open source and closed source.
Keywords: Vulnerabilities; security; open source software; closed source software; empirical comparison

Offshore measurements in the Baltic Sea - Bendfeld, Jörg; Tigges, Martin; Voss, Jürgen (World Sustainable Energy Days (WSED 2009), Wels, Austria, Februar 2009)

Effizientere Nutzung der Offshore-Windenergie durch die Kombination mit Biogaskraftwerken - Bendfeld, Jörg; Tigges, Martin; Voss, Jürgen (VDI Kongress AUTOMATION 2009, Baden-Baden, Deutschland, Juni 2009)

Effects of Offshore Wind Energy Fluctuations on the Intra-day spot-market in Germany - Bendfeld, Jörg; Splett, Michael (10th IAEE European Conference (International Association for Energy Economics): Energy, Policies and Technologies for Sustainable Economies; Wien, Österreich, September 2009)

Reduction of CO2 Emission of conventional utilities using offshore wind energy - possibilities and prospects - Bendfeld, Jörg; Splett, Michael (European Offshore Wind 2009 Conference & Exhibition (EoW))

Smoothing effects of the natural combination potential at spacious distributed offshore wind farms to reduce the input variability - Bendfeld, Jörg; Splett, Michael (Proceedings of the European Offshore Wind 2009 Conference & Exhibition (EoW))

The influcence of offshore wind energy on pricing at the intra-day spot market in Germany - Bendfeld, Jörg; Splett, Michael (Proceedings of the European Offshore Wind 2009 Conference & Exhibition (EoW))

Reducing the Feed-in Fluctuations of Offshore Wind Farms by Biogas Plants - Bendfeld, Jörg; Tigges, Martin; Splett, Michael; Voss, Jürgen (Proceedings of the WORLD ENERGY ENGINEERING CONGRESS, Washington Convention Center, Washington, DC, November 2009)

FLUKTUATIONSKOMPENSATION DER OFFSHORE-WINDENERGIE MITTELS VERTEILTER BIOGASKRAFTWERKE - Bendfeld, Jörg; Splett, Michael; Tigges, Martin (IRES 2009: 4. Internationale Konferenz zur Speicherung Erneuerbarer Energien, Berlin)

Comparison of module temperature measurement methods. - Krauter, Stefan; Preiss, A. (Proceedings of the 34th IEEE Photovoltaic SpecialistsConference, Philadelphia (USA), June 7-12,2009)

Individuelle Förderung - Einblicke in Strukturen und erste empirische Ergebnisse des Modellprojekts InLab - Beutner, Marc; Frehe, Petra; Kremer, H.-Hugo; Zoyke, A. (Kölner Zeitschrift für Wirtschaft und Pädagogik)

Berufsbildung im Justizvollzug - Das Projekt TANDEM - Beutner, Marc; Gebbe, M.; Kremer, H.-Hugo (Kölner Zeitschrift für Wirtschaft und Pädagogik)

Individuelle Förderung von Kompetenzen - Curriculare und didaktisch-methodische Optionen - Kremer, H.-Hugo; Zoyke, Andrea (Erziehungswissenschaft und Beruf)

Shelagh Delaney 'A Taste of Honey' - Tönnies, Merle (Kindlers Literaturlexikon)

David Hare 'A Map of the World' - Tönnies, Merle (Kindlers Literaturlexikon)

David Hare 'Knuckle' - Tönnies, Merle (Kindlers Literaturlexikon)

David Hare 'Plenty' - Tönnies, Merle (Kindlers Literaturlexikon)

Ann Patricia Jellicoe 'The Knack' - Tönnies, Merle (Kindlers Literaturlexikon)

Stephen Poliakoff 'Strawberry Fields' - Tönnies, Merle (Kindlers Literaturlexikon)

Peter Shaffer 'Amadeus' - Tönnies, Merle (Kindlers Literaturlexikon)

Peter Shaffer 'Equus' - Tönnies, Merle (Kindlers Literaturlexikon)

George Bernard Shaw 'Mrs Warren's Profession' - Tönnies, Merle (Kindlers Literaturlexikon)

Oscar Wilde 'Mrs Henry Wood' - Tönnies, Merle (Kindlers Literaturlexikon)

Bewältigung beruflicher Übergänge im Lebensverlauf - Kremer, H.-Hugo (Bildungsperspektiven in alternden Gesellschaften)

Performative Lebensbewältigung in alternden Gesellschaften: Projektbeschreibung und Einführung in den Tagungsband - Dehmel, A.; Kremer, H.-Hugo; Schaper, N.; Sloane, Peter F. E. (Bildungsperspektiven in alternden Gesellschaften)

Implementation von E-Learning an Berufskollegs - eine Studie zu Stand und Entwicklungsperspektiven in Ostwestfalen-Lippe - Kremer, H.-Hugo; Zoyke, A. (Wirtschaft und Erziehung)

Optimal strategies for maintaining a chain of relays between an explorer and a base camp - Kutyłowski, Jarosław; Meyer auf der Heide, Friedhelm (Theoretical Computer Science)

Power-aware online file allocation in mobile ad hoc networks - Mehler, Jan; Meyer auf der Heide, Friedhelm (Proceedings of the twenty-first annual symposium on Parallelism in algorithms and architectures - SPAA '09)

Proceedings of the twenty-first annual symposium on Parallelism in algorithms and architectures - SPAA '09

A Birkhoff–Lewis Type Theorem for the Nonlinear Wave Equation - Biasco, Luca; Di Gregorio, Laura (Archive for Rational Mechanics and Analysis)

Multiobjective optimization for transistor sizing of CMOS logic standard cells using set-oriented numerical techniques - Blesken, Matthias; Ruckert, Ulrich; Steenken, Dominik; Witting, Katrin; Dellnitz, Michael (2009 NORCHIP)

Computation of robust Pareto points - Dellnitz, M.; Witting, K. (International Journal of Computing Science and Mathematics)

On the Approximation of Transport Phenomena - a Dynamical Systems Approach - Dellnitz, Michael; Froyland, Gary; Horenkamp, Christian; Padberg, Kathrin (GAMM-Mitteilungen)

Seasonal variability of the subpolar gyres in the Southern Ocean: a numerical investigation based on transfer operators - Dellnitz, M.; Froyland, G.; Horenkamp, C.; Padberg-Gehle, K.; Sen Gupta, A. (Nonlinear Processes in Geophysics)

A multi-objective approach to the design of low thrust space trajectories using optimal control - Dellnitz, Michael; Ober-Blöbaum, Sina; Post, Marcus; Schütze, Oliver; Thiere, Bianca (Celestial Mechanics and Dynamical Astronomy)

Symmetries in Timed Continuous Petri Nets - Meyer, A.; Dellnitz, M. (IFAC Proceedings Volumes)

Who is on my Team: Building strong Teams in Interdisciplinary Visualization Courses - Domik, Gitta (ACM SIGGRAPH ASIA 2009 Educators Program)

Local expansion concepts for detecting transport barriers in dynamical systems - Padberg, Kathrin; Thiere, Bianca; Preis, Robert; Dellnitz, Michael (Communications in Nonlinear Science and Numerical Simulation)